Efficacy and safety of intravenous mesenchymal stem cells for ischemic stroke patients, a systematic review and meta-analysis - Hassanein, Maged Elsayed; Fayad, Jaber; Shabana, Jilan Ali; AlEdani, Esraa M.; Hefnawy, Mahmoud Tarek; Ghaith, Hazem S.; Negida, Ahmed (Frontiers in Stroke, 2024)
Clinical trials evaluated the efficacy of intravenous mesenchymal stem cells (MSCs) for acute and subacute ischemic stroke. Therefore, we conducted this meta-analysis to investigate the efficacy and safety of intravenous mesenchymal stem cells compared to placebo for acute and subacute ischemic stroke patients.We searched PubMed, SCOPUS, Web of Science, and Cochrane CENTRAL for randomized controlled trials evaluating any clinical trial of intravenous mesenchymal stem cells for acute and subacute ischemic stroke patients. The efficacy outcomes of this study were the rates of improvement in the NIH stroke score (NIHSS), the good Modified Rankin scale (mRS), andThe Barthel index, while the safety outcomes were the rates of mortality and stroke recurrence. We compared intravenous mesenchymal stem cells and placebo on a fixed effect meta-analysis model in R software.Four RCTs with 97 patients were included in the analysis. In the meta-analysis, MSCs were superior to placebo in good Modified Rankin Scale (mRS) (MD -0.95, 95% CI [-1.39; -0.52])or Barthel index (BI) (MD 21.36, 95% CI [9.96; 32.75]), and MSCs was not superior to placebo in the rate of improvement of the National Institutes of Health Stroke Scale (NIHSS) (MD -1.81, 95% CI [-4.123; 0.494]). The MSCs were neither associated with decreased mortality nor Stroke recurrence (RR 0.58 and 0.59, respectively, P value = 0.51 and P value = 0.533).For patients with acute and subacute ischemic stroke who are eligible for further damage to neural tissue, MSCs achieve high efficacy and acceptable safety.